Catholic Inculturation in Ganjuran: A Study of Culture and Its potential as BIPA Teaching Material - Nova Diadara; Tedi Permadi; Yulianeta; Do Tuyet Ngan (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
Gereja Hati Kudus Tuhan Yesus (GHKTY) provides a resource for intercultural learning, particularly in the teaching of Indonesian as a Foreign Language (BIPA). In this paper, we have examined the culture and practices of Javanese Catholics in Ganjuran and what it means for BIPA teachers to teach them in this context. The study was conducted with a qualitative approach based on ethnography and participant observation, in-depth interviews, and documents from liturgical archives. The results show that Javanese Catholicism in Ganjuran is a kind of living folklore that combines faith and culture in the form of performative acts, architectural symbols, and oral tradition. Theoretically, this study extends the notion of folklore performance as an inculturative process that involves theology, culture, and pedagogy. Methodologically, it highlights the importance of focused ethnography for the study of religious folklore. Practically, Ganjuran is a cultural learning site where faith, language, and identity come together in a culture-shaping, theo-cultural environment.